Physical attractiveness, employment and earnings - Christian Pfeifer (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2011)
Survey data is used to estimate the impact of physical attractiveness rated by the interviewer as well as by the respondent on employment probability and labor income of men and women. In addition to mean linear and non-linear effects on earnings, simultaneous quantile regressions are applied to analyze heterogeneity across the wage distribution.
Keywords: J31; J71; J10; 330; Attractiveness; Beauty; Employment; Wages; Menschen; Arbeitsnachfrage; Lohndifferenzierung; Deutschland